Developing critical reading and thinking skills using reading and critical thinking exercises Ramakian at Narai Prabnontok together with Kahoot game for 2nd year high school students. - Kinnareewong, Sunantha; Pengteee, Sayjai; Lunsopa, Dechsit (Journal of Research and Development Institute Rajabhat Maha Sarakham University, 2024)
The objectives of this research were 1) to develop a reading and critical thinking exercise in literature; 2) To compare the reading and analytical skills of students who learned by using the reading and analysis skills of the literature titled Ramakian at Narai Prabnontok together with the use of Kahoot games before and after class 3) To study the satisfaction of students who learned by practicing reading and analyzing the value of literature. Ramakian at Narai Prabnontok in conjunction with Kahoot The sample used in this development was 40 students in Year 2/5 of Roi Et College for the academic year 2022 from cluster sampling using classrooms as random units. The tools used in the development include: 1) 6 learning management plan for secondary school year 2, 6 hours plan, 1) learning management plan 1, practice analyzing the value before learning from Ramayana, learning management plan 2, history of Ramakian at Narai Prabnontok, learning management plan 3, study the story, disconnect wisdom, learning management plan 4, learn value. Ramakian at Narai Prabnontok Learning Management Plan 5: Finding Value from Kahoot and Learning Management Plan 6: Practice analyzing value after learning from Ramayana. 2) Reading and thinking skills to analyze the value of literature Ramakian at Narai Prabnontok For secondary school 2, 2 sets of 20 questions are divided into 1 set of 10 questions and 1 set of 10 Kahoot exercises 3) Satisfaction questionnaire of secondary school students of Roi Et College, Roi Et Province, academic year 2022. Ramakian at Narai Prabnontok together with the use of Kahoot game as a rating scale of 5 levels of 4 aspects and 18 items can summarize the results of the study as follows: The results of the reading and thinking exercises analyze the value of literature. Ramakian at Narai Prabnontok, together with the use of Kahoot games for secondary school students to be effective according to the 80/80 criteria, found that the effectiveness of the reading and critical thinking exercises for the value of literature. Ramakian at Narai Prabnontok (E1/E2) is equal to 81.62/98.38, which is higher than the set 80/80 threshold. Comparative analysis of reading and critical thinking skills of students who learned by practicing reading and thinking to analyze the value of literature. Ramakian at Narai Prabnontok, together with Kahoot after school, was statistically significantly higher than pre-school at .01. Comparative analysis of reading and critical thinking skills of students who learned by practicing reading and thinking to analyze the value of literature. Ramakian at Narai Prabnontok, together with Kahoot after school, was statistically significantly higher than pre-school at .01. The results of the analysis of the satisfaction of students studied by the reading exercises analyzed the value of literature. Ramakian at Narai Prabnontok in conjunction with the use of Kahoot game at the highest level ( = 4.66, S.D. = 0.53 ) When considering the details, it was found that 1) the satisfaction with the skill exercises; Students had the highest level of overall satisfaction ( = 4.55, S.D. = 0.60), 2) Reliance on Kahoot games, students had the highest level of overall satisfaction ( = 4.70, S.D. = 0.47), 3) Satisfaction with teachers. Learners are most satisfied ( = 4.74 , S.D. = 0.52 ).